PENGARUH BUDAYA KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT KARYA ABADI MAKMUR (SNAPY) JAKARTA SELATAN - Renaldy Bagag M; Suprapto (Journal of Research and Publication Innovation, 2025)
The purpose of this study was to determine the effect of work culture and work discipline on employee performance at PT Karya Abadi Makmur (SNAPY) South Jakarta. The method used is quantitative. The sampling technique uses saturated samples, namely 73 employees. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, autocorrelation tests, determination coefficients and hypothesis tests. The results of this study are that work culture has a significant effect on employee performance with a determination coefficient value of 46.9% and the hypothesis test obtained t count> t table or (7.914> 2.646). Work discipline has a significant effect on employee performance with a determination coefficient value of 46.0% and the hypothesis test obtained t count> t table or (7.784> 2.646). Work culture and work discipline simultaneously have a significant effect on employee performance with a regression equation Y = 4.990 + 0.474 X1 + 0.386 X2 + α. The coefficient of determination value is 55.3% while the remaining 54% is influenced by other factors. The hypothesis test obtained the calculated F value > F table or (43.271 > 3.120).